A Systematic Review of Entrepreneurship Development in Coastal Communities: Implications for Women's Empowerment in the Bajo Tribe in Waktobi Regency - Surni, Surni; Sukristyanto, Agus; Novaria, Rachmawati (International Journal of Educational Research & Social Sciences, 2024)
This study looks at how entrepreneurship develops in coastal communities. The method uses bibliometric analysis of academic literature from the Scopus database from 2004 to 2024. This approach helped identify patterns, key themes and relationships in the study of entrepreneurship in coastal areas. The data were analysed using software such as RStudio, VOSviewer, and CiteSpace to show trends, networks, and how concepts change in the literature. The most discussed topics were climate change, tourism and sustainable development. The issue of women's empowerment and the role of micro, small and medium enterprises (MSMEs) received more attention in recent years. The research also found that coastal entrepreneurship is becoming more holistic, integrating social, economic and environmental aspects. This research shows that public policies should support entrepreneurship in coastal communities, especially those involving women. However, this study only looked at a few coastal communities, so the results may not apply to other areas. Further research is needed to cover more areas and compare different coastal communities.